Antimicrobial and Volatile Compounds Study of Four Spices Commonly Used in Indonesian Culinary - Hamad, Alwani; Mahardika, M. Gigih Panji; Istifah, Istifah; Hartanti, Dwi (Fakultas Farmasi, Universitas Gadjah Mada, 2016)
The n-hexane extracts of the aerial parts of Ocimum x citriodorum and the leaves of Cymbopogon citratus, Syzygium aromaticum and Syzygium polyanthum were evaluated for their antimicrobial activity against some food borne microorganisms. Their volatile compounds were analyzed by gas chromatography/mass spectrometry (GC/MS). All extracts inhibited the growth of Bacillus subtilis. The extract of S. polyanthumÂ showed the strongest inhibitory activity againstÂ Salmonella typhimurium. The growth of Staphylococcus aureus, Escherichia coli and Vibrio cholera were not inhibited by all extracts. The major volatile constituent of O. x citriodorum, C. citratus, S. aromaticum and S. polyanthumÂ crude extracts were citral, germacrene D-14-ol, p-eugenol and squalene, respectively.